190 THE USEFULNESS OF A BILATERAL TRANS-CERVICAL PNEUMOMEDIASTINAL APPROACH FOR MEDIASTINOSCOPIC RADICAL ESOPHAGECTOMY. (17th September 2021) - Tokairin, Yutaka; Nakajima, Yasuaki; Kawada, Kenro; Hoshino, Akihiro; Okada, Takuya; Matsui, Toshihiro; Yamaguchi, Kazuya; Nagai, Kagami; Kinugasa, Yusuke
Abstract: : Several authors have reported on the left trans-cervical and transhiatal approaches under pneumomediastinum and right cervical open surgery for mediastinoscopic esophagectomy. However, with these approaches, sufficient dissection of the right upper mediastinal paraesophageal lymph nodes, right recurrent nerve lymph nodes and the subaortic arch to the left tracheobronchial lymph nodes is thought to be difficult. We herein report the usefulness of the 'bilateral' trans-cervical pneumomediastinal approach. Methods: Ten patients with thoracic esophageal cancer were treated using this approach. Under pneumomediastinum via a right neck incision, the right cervical and upper mediastinal paraesophageal lymph nodes were dissected. The left recurrent nerve lymph nodes were dissected using a left trans-cervical pneumomediastinal approach. The subaortic arch to the left tracheobronchial lymph nodes was dissected with a combined right and left trans-cervical crossover approach. After this approach, thoracoscopic observation was then performed in the left decubitus position, and if the lymph nodes were not sufficiently dissected, the remnant lymph nodes were retrieved thoracoscopically. Results: The average total number of dissected lymph nodes among the right cervical and upper mediastinal paraesophageal lymph nodes identified with a right cervical open/right trans-cervical mediastinoscopic/right thoracoscopic approach was 3.2/4.0/0.6, respectively. The average total number of dissected lymph nodes among the subaortic arch to the left tracheobronchial lymph nodes with a right trans-cervical mediastinoscopic/right thoracoscopic approach was 1.5/0.6, respectively. These findings indicate that, without the right trans-cervical pneumomediastinal approach, roughly four of the right cervical and upper mediastinal paraesophageal lymph nodes and one or two of the subaortic arch to the left tracheobronchial lymph nodes could not have been retrieved. Conclusion: A bilateral trans-cervical pneumomediastinal approach is useful for achieving sufficient upper mediastinal lymph node dissection and esophagectomy.